2023
DOI: 10.1186/s12877-023-03799-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of decreased intrinsic capacity: Performance of diagnostic measures of the ICOPE Screening tool in community dwelling older people in the VIMCI study

Abstract: Background The World Health Organization (WHO) has developed the Integrated Care for Older People (ICOPE) strategy to face the challenges of ageing societies. This strategy is focused on person centered care and the assessment intrinsic capacity (IC). Early identification of five domains of IC (cognition, locomotion, vitality, sensory (hearing and vision), and psychological) has been shown to be related with adverse outcomes and can guide actions towards primary prevention and healthy ageing. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…Among the seven IC-related components, six predictors expect vision capacity were identified to be significantly associated with the functional abilities in varied contribution. The results are consistent with a study assessing the performance of diagnostic measures of the ICOPE screening tool in European community-dwelling older adults, which showed only vision, but not other IC-related domains vision, had the lowest sensitivity among all IC domains between normal and altered population [ 46 ]. Among all IC predictors in the scoring algorithm, locomotion weighted most in predicting IADL and frailty.…”
Section: Discussionsupporting
confidence: 90%
“…Among the seven IC-related components, six predictors expect vision capacity were identified to be significantly associated with the functional abilities in varied contribution. The results are consistent with a study assessing the performance of diagnostic measures of the ICOPE screening tool in European community-dwelling older adults, which showed only vision, but not other IC-related domains vision, had the lowest sensitivity among all IC domains between normal and altered population [ 46 ]. Among all IC predictors in the scoring algorithm, locomotion weighted most in predicting IADL and frailty.…”
Section: Discussionsupporting
confidence: 90%
“…Studies that used the Step 1 screen as designed reported lower prevalence rates of cognitive loss (e.g. 20.3% in Taiwan, 37 24.3% in Hong Kong 38 and 31% in Spain 39 ) compared with studies that estimated cognitive loss based on the Step 1 screen derived from MMSE (e.g. 52.2% in France 40 ).…”
Section: Discussionmentioning
confidence: 97%
“…A study in Spain [ 12 ] enrolled 207 older people aged ≥ 70 years, based on the WHO IC assessment pathway, including screening and detailed evaluation of vision and hearing. The results revealed that among all dimensions, the cognitive domain had the highest sensitivity (0.889), with the other dimensions ranging from 0.438–0.557.…”
Section: Discussionmentioning
confidence: 99%
“…However, what is the diagnostic performance of the ICOPE screening tool in detecting IC decline? There are two published studies, one from Hong Kong, China [ 11 ], and the other from Spain [ 12 ]; both of them indicate that the ICOPE screening tool has high sensitivity but varying screening effectiveness across different dimensions. Additionally, no relevant studies have been conducted in mainland China.…”
Section: Introductionmentioning
confidence: 99%